Pengembangan Potensi Santri di Pondok Pesantren Nurul Huda Tegalsambi Jepara - Affni, Fitri Sorelah; Laila, Azzah Nor (Rumah Jurnal Institut Agama Islam An-Nawawi Purworejo, 2024)
Currently, Islamic boarding schools are used as one of the non-formal educational institutions to increase the potential of students to be able to compete in the era of globalization, such as the Nurul Huda Tegalsambi Jepara Islamic boarding school. The purpose of this article is to find out about the development of students carried out by the Nurul Huda Tegalsambi Jepara Islamic boarding school, the potential that is formed through activities at the Nurul Huda Tegalsambi Jepara Islamic boarding school and what are the supporting and inhibiting factors for realizing the development of the potential of students at the Nurul Huda Tegalsambi Jepara Islamic boarding school. This research was carried out using a descriptive qualitative approach which aims to understand an event or occurrence experienced by the research subject. Data collection techniques are observation, interviews and documentation. The analysis used is reduction, presentation and drawing conclusions or verification. The results of the research show that the development of the potential of students at the Nurul Huda Tegalsambi Jepara Islamic boarding school is through several activities that differentiate it from the Nurul Huda Islamic boarding school, such as khitobah, recitation of Muslim mothers and teaching at Diniyah madrasas, then the potential is formed from the development of the students' potential and supporting factors for development. Potential includes the wishes of Islamic boarding school caregivers, consistency, adequate facilities and infrastructure, support from the community and religious leaders. Meanwhile, inhibiting factors include students lacking discipline and responsibility, lack of awareness and sincerity within students.